French Chivalry : Chivalric Ideas and Practices in Mediaeval France - Painter, Sidney, 1902-1960 (Book collections on Project MUSE., 2019)
Chivalry denotes the ideals and practices considered suitable for a noble. The word itself is reminiscent of the aristocratic society of medieval France dominated by mounted warriors. As early as the eleventh century, several different views of chivalric standards and behavior had appeared. During the next four hundred years, these conceptions of the ideal nobleman were developed by and for the feudal ruling class. Sidney Painter studies chivalry from the perspectives of both social history and the history of ideas. The first chapter provides readers unfamiliar with medieval history the background required for understanding the chapters on chivalry.